2020
DOI: 10.1002/jpen.1938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exclusive Enteral Nutrition on the Disease Process, Nutrition Status, and Gastrointestinal Microbiota for Chinese Children With Crohn's Disease

Abstract: Background:The aim of this study was to prospectively study the effect of exclusive enteral nutrition (EEN) treatment on Chinese pediatric Crohn's disease (CD) patients. Methods: Thirty-one newly diagnosed CD patients were enrolled in this study and treated with EEN for 8 weeks. Twelve healthy controls (HCs) donated their fecal samples. Statistical methods were used to compare the differences. Results: According to the Simple Endoscopic Score for CD (SES-CD) at the end of the EEN treatment, 21 patients with SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…Therefore, it is necessary to infuse the nutrient solution evenly and in time and secure catheter properly. Parenteral nutrition requires regular pulse pressing flushing and strict aseptic operation principles [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to infuse the nutrient solution evenly and in time and secure catheter properly. Parenteral nutrition requires regular pulse pressing flushing and strict aseptic operation principles [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children responding to EEN have a statistically significant improvement in weight and body mass index z ‐scores over the course of therapy, 4,5 which are sustained over a 6‐month period 4 . In a Chinese study, children who reached remission after an 8‐week course of EEN had statistically significant improvement in weight gain, haemoglobin and serum albumin level, compared with children who did not reach remission on EEN ( P < 0.05) 22 …”
Section: Resultsmentioning
confidence: 99%
“…Four studies identified a significantly higher rate of mucosal healing in children who received EEN as induction therapy, compared to CS 18,20,21,22 …”
Section: Resultsmentioning
confidence: 99%
“…However, there are very few studies provided information on mucosal healing of patients at the end of induction. Several studies in western countries have found that EEN can induce early mucosal healing rate of 18.9%-58% (3,14).…”
Section: Discussionmentioning
confidence: 99%